2010
DOI: 10.1016/j.bone.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Transient muscle paralysis disrupts bone homeostasis by rapid degradation of bone morphology

Abstract: We have previously shown that transient paralysis of murine hindlimb muscles causes profound degradation of both trabecular and cortical bone in the adjacent skeleton within 3 weeks. Morphologically, the acute loss of bone tissue appeared to arise primarily due to osteoclastic bone resorption. Given that the loss of muscle function in this model is transient, we speculated that the stimulus for osteoclastic activation would be rapid and morphologic evidence of bone resorption would appear before 21 d. We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
90
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 41 publications
15
90
3
1
Order By: Relevance
“…Given that current HO treatments such as radiation and nonsteroidal antiinflammatory drugs have potentially severe side effects [5,6,24], transient muscle paralysis and/or focal inhibition of neuromuscular signaling presents an alternative intervention with potential for preventing heterotopic bone after orthopaedic trauma. However, translation of this approach to the clinic will require a better understanding of the cellular mechanisms controlling muscle/bone/nerve interactions so that optimal inhibition of HO can be achieved while the potentially adverse effects of transient neuromuscular inhibition are minimized [2,23].…”
Section: Discussionmentioning
confidence: 99%
“…Given that current HO treatments such as radiation and nonsteroidal antiinflammatory drugs have potentially severe side effects [5,6,24], transient muscle paralysis and/or focal inhibition of neuromuscular signaling presents an alternative intervention with potential for preventing heterotopic bone after orthopaedic trauma. However, translation of this approach to the clinic will require a better understanding of the cellular mechanisms controlling muscle/bone/nerve interactions so that optimal inhibition of HO can be achieved while the potentially adverse effects of transient neuromuscular inhibition are minimized [2,23].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of NICD from the targeted Rosa26 locus occurs following the excision of the STOP cassette by Cre recombination of loxP sequences (35,36 Muscle Immobilization Protocol-The effect of muscle immobilization on the skeleton was tested in 1-month-old Dmp1-Cre ϩ/Ϫ ;Rosa Notch and littermate control male mice. For this purpose, control and experimental mice were injected with botulinum toxin A (BtxA) (Allergan Inc., Irvine, CA) at a dose of 2 units/100 g of body weight administered in equal amounts in the quadriceps and the triceps surae muscle groups or injected with saline under anesthesia using a ketamine/xylazine mixture intraperitoneally (37)(38)(39)(40). The contralateral limb was used as an internal control.…”
Section: ;Notch2mentioning
confidence: 99%
“…In our previous studies (Poliachik et al 2010), a serial time point design yielded much more consistent results, in which the affected limb was scanned before the experiment and at specific time points thereafter to assess bone changes within the limb. Therefore, the fact that in the present study one of the metrics of bone loss (BS/BV) reached statistical significance between Obtxand FUS-treated groups, and other metrics indicated a trend toward statistical significance, suggests that with a better choice of the control, the results may have reached statistical significance.…”
Section: Discussionmentioning
confidence: 91%
“…To model appendicular bone loss, we employed a mouse model of disuse using onabotulinumtoxinA (Obtx) to induce paralysis of the calf muscle, which results in rapid degradation of trabecular bone in the proximal tibia (Poliachik et al 2010;Warner et al 2006) This model has been found to reduce, but not remove, ground reaction forces in the affected limb (Manske et al 2011).The resulting maximum trabecular bone loss in this model occurs approximately 12 d after Obtx injection; an average of 77% trabecular bone volume was lost in C57B6 mice. Pulsed focused ultrasound (pFUS) mimicking physiologic muscle contraction rates or LIPUS frequency for fracture healing (1 kHz) (Azuma et al 2001;Leung et al 2004b) was applied to the calf muscle after paralysis in an attempt to mitigate the associated bone loss.…”
Section: Introductionmentioning
confidence: 99%